A new family of bidirectional DC-DC power converters with very low input and output ripples - Muhammad Nuruddin Ar Rabbani; Andriazis Dahono; Arwindra Rizqiawan; Pekik Argo Dahono (Universitas Ahmad Dahlan, 2022)
Bidirectional DC-DC converters with very low ripple contents in the input and output sides are desirable in many applications. This paper proposes a new family of bidirectional DC-DC converters with very low input and output ripples that is derived from the conventional Cuk DC-DC converter. At first, a new family of single-phase DC-DC converter is derived. Then, extension of this family into the multiphase ones is presented. Output voltage expressions of the proposed DC-DC converters are presented. It is found that the derived DC-DC converters have lower conduction losses than the conventional DC-DC converters. Expressions of input and output ripples of the proposed DC-DC converters are then also presented. Finally, some experimental results are included to show the basic performance of the proposed converters. Thus, the outcome of the proposed DC-DC converter can be achieved by using the duty ratio is half and the multiphase technique is upper-middle inductors. It given that the current and voltage ripples of proposed DC-DC converter is very low and almost zero.